Implementing the Merdeka Curriculum in English Language Teaching at Rumah Belajar Aksi-Inspirasi: A Case Study of Strategies and Challenges - Haan, Videlindah Ani Sophiandry; Margana, Margana; Apriliani, Maria Kanisia (Universitas Pendidikan Mandalika, 2025)
The primary aim of this study was to explore the implementation of the Merdeka Curriculum in English language teaching at Rumah Belajar-Aksi Inspirasi, focusing specifically on the development of lesson plans, the instructional process, and the assessment strategies employed by three English teachers in Sleman, Yogyakarta, Indonesia. This qualitative case study utilized descriptive analysis, employing structured interviews, classroom observations, and an analysis of instructional documents for data collection. The findings reveal that teachers implement the Merdeka Curriculum through three primary strategies: CERIA, Game-Based Learning (GBL), and Jigsaw. They adapt textbooks provided by the Indonesian Ministry of Education and Culture to fit their classroom context and incorporate a range of educational tools, including laptops, cell phones, and interactive websites such as Wordwall, Gemary, and Quiz. Both formative and summative assessments are conducted at the end of each session, resulting in 85% of students demonstrating increased engagement and comprehension. The study highlights the significance of these strategies in enhancing the teaching and learning process and offers insights into the effective implementation of the Merdeka Curriculum in English language education.Â